قانون الأعداد الكبيرة للدوال العشوائية بمتحولين - سويقات, محمد; علي, وديع; صالح, نغم (Latakia University Journal -Basic Sciences Series, 2013)
نقوم في هذا البحث بإيجاد قانون الأعداد الكبيرة للدوال العشوائية المحدبة – المقعرة المغلقة و نعمِّم بعض النتائج المتعلقة بالدوال نصف المستمرة من الأدنى ذات المتحول الواحد إلى نتائج مشابهة تخص دوال محدبة – مقعرة بمتحولين وذلك باستخدام الدوال القرينة المحدبة لدالة محدبة – مقعرة وتقارب موسكو فوق /تحت البياني . In this research we will find a law of the large numbers for random convex – concave closed functions , and generalize some results related to lower semi- continuous functions to similar results concerning the convex– concave functions , and that will be done with using the parent convex functions and the Mosco-epi \ hypo-convergence .